Hubungan Kondisi Sarana Sanitasi Wisata (Sarsanta) dengan Tingkat Kepuasan Wisatawan Kawasan Wisata Waduk Gajah Mungkur di Kabupaten Wonogiri - Nur Rohmad; Purwanto Purwanto; Herman Santjoko (Poltekkes Kemenkes Yogyakarta, 2014)
Sanitation at tourists places is one effort of the application of public places sanitation, which is useful for the convenience, safety and satisfaction of tourists. Based on the preliminary survey conducted at Gajah Mungkur Tourists Area in Wonogiri, some problems were found regarding with the provision of sanitation facilities. The study was aimed to know the condition of sanita-tion facilities in two tourists destination there, i.e. Sendang Asri Recreation Park and Gajah Mungkur Waterboom as well as to know the satisfaction level of the visiting tourists, by con-ducting a cross sectional designed survey, whose results were analyzed descriptively and ana-litically. The respondents, who were interviewed for determining the satisfaction level, were 82 tourists who had visited the two sites, meanwhile, the condition of the facilities were measured by using the standard check-list. Results of the study showed that the sanitation condition in Sendang Asri was classified as “not properly healthy”, and in Waterboom was classified as “properly healthy”. The tourists who satisfied with sanitation facilities in Sendang Asri and Wa-terboom, were 37,80 % and 89,02 % respectively. The result of statistical test by employing chi-square test at 95 % confidence level, concluded that sanitation facility condition has significant correlation with tourists’ satisfaction level. Based on these findings, management of the two re-sorts and Tourism Agency of Wonogiri Regency were advised to upgrade the condition of sani-tation facilities in Gajah Mungkur Tourists Area.